2014
DOI: 10.1021/am501610p
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Aminated Poly(phenylene sulfide)/ZnO Nanocomposites for Medical Applications

Abstract: An aminated poly­(phenylene sulfide) derivative (PPS-NH2) has been melt-blended with different contents of ZnO nanoparticles, and the morphology, thermal, mechanical, tribological, antibacterial, and dielectric properties of the resulting nanocomposites have been investigated. The nanoparticles were dispersed within the matrix without the need for surfactants or coupling agents. A gradual rise in the crystallization temperature and the degree of crystallinity was found with increasing ZnO loading, confirming t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 49 publications
(98 reference statements)
4
59
0
1
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12]14,16 In particular, the inorganic fillers, including BaTiO 3 , 4−7,15 SrTiO 3 , 16−18 Pb(Zr x Ti 1−x )O 3 −PbTiO 3 , 19 AlTiO 3 , 20,21 Al 2 O 3 , 10,11,22 ZrO 2 , 10,23 MgO, 10,11 and their mixtures, 10,11,19,24 have been extensively used as dielectric capacitors owing to their high dielectric permittivity of several hundreds. Marks et al reported that the BaTiO 3 − and ZrO 2 − Al 2 O 3 nanoparticles can significantly improve the dielectric permittivity and energy density of the PP nanocomposites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12]14,16 In particular, the inorganic fillers, including BaTiO 3 , 4−7,15 SrTiO 3 , 16−18 Pb(Zr x Ti 1−x )O 3 −PbTiO 3 , 19 AlTiO 3 , 20,21 Al 2 O 3 , 10,11,22 ZrO 2 , 10,23 MgO, 10,11 and their mixtures, 10,11,19,24 have been extensively used as dielectric capacitors owing to their high dielectric permittivity of several hundreds. Marks et al reported that the BaTiO 3 − and ZrO 2 − Al 2 O 3 nanoparticles can significantly improve the dielectric permittivity and energy density of the PP nanocomposites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1c) contains the characteristic peaks of the imine base ligand such as C = N, C = C and C = O stretching vibration peak at 1598, 1555 and 1647 cm −1 , respectively. The peak at 450 cm −1 corresponded to Zn-O stretching [29]. The surface morphology and particle size of Fe 3 O 4 @MAA@IBL nanostructure were studied by SEM and TEM images.…”
Section: Characterization Of the Sorbentmentioning
confidence: 99%
“…Poly(1,4‐phenylene sulfide) (PPS) is widely applied in food industry, mechanical and chemical engineering, automobile, electronics, aerospace engineering, and so on nowadays as a special kind of semicrystalline engineering thermoplastic, due to its excellent chemical resistance, good thermal property, and low toxicity . However, the pure PPS cannot be used widely in the world because of its brittleness .…”
Section: Introductionmentioning
confidence: 99%